Análisis del procedimiento legal establecido para la legalización de la concesión, uso y aprovechamiento de aguas, en el sector rural” Investigador - Cobos Castillo, Geovany Jesús (2023)
the legalization of the concession, use and exploitation of water in the rural sector" a detailed study will be carried out about the legal procedure that is carried out today, according to the new restructuring of the State, in the Ministry of the Environment, through the Water Regulation and Control Agency, which is currently in charge of everything that has to do with the legalization of the concession, use and exploitation of water in the rural sector . It is an analysis from the perspective of the constitutional principle of equity of the procedure that must be carried out to legalize the use, enjoyment and exploitation of water for crops, animal watering troughs, fish farming, etc.; productive activities that contribute to the local, provincial and national economy. However, it is evident that there are differences between large, medium and small producers, all these sectors have an implicit need to use water from rivers and natural springs to be able to carry out their activities in a normal way. It is necessary to carry out a technical-legal analysis about respect for equity in the concession for the use, enjoyment and exploitation of water; so it is within this scope that the procedure will be analyzed in the context of the pertinent regulations and how the procedure is carried out in the Water Regulation and Control Agency, because cases are continuously presented in which large properties affect the most small and with it there is an affectation to the right to access the vital resource with equity. For some time now, it has been determined that the use, enjoyment and exploitation of water should be legalized as a regulation and control mechanism; but this, in addition to being regulated, must respect conditions, needs, and purposes of productivity, of the use of the vital resource. This is where this investigation was born, which aims to determine the suitability of the procedure and at the same time determine aspects that must be inserted so that the procedure for concession, use, enjoyment and exploitation of water is equitable and is attached to due process. 5 The methodologies to be used in this investigative work are qualitative and quantitative, since the facts and social phenomena that I will study in this work are measurable and quantifiable. In this way, I will also measure and establish causal relationships between the variables, to explain the study problem and the current social reality. I will apply the dogmatic and interpretive methods, since through these methods an answer to the problem treated is offered from what it is believed to be the best possible reconstruction allowed by the legal material available. Keywords: Legalization, Concession, Exploitation, Equity, Efficacy